Regulation of mouse serum amyloid A gene expression in transfected hepatoma cells. - Huang, J H (1990)
Expression of mouse serum amyloid A (SAA1, -2, and -3) mRNAs can be induced up to 1,000-fold in the liver in response to acute inflammation. This large increase is primarily the result of a 200-fold increase in the rates of SAA gene transcription. To analyze the cis-acting regulatory element(s) responsible for regulating transcription, we fused 306 base pairs of the mouse SAA3 promoter to a reporter gene, the chloramphenicol acetyltransferase (CAT) gene, and transfected this chimeric DNA into cultured cells. In transient expression assays, this 5' sequence was sufficient to confer cell-specific expression: CAT activity was readily detectable when the construct was transfected into liver-derived cells but was not detectable in nonliver cells. Furthermore, when liver cells transfected with this construct were treated with conditioned media prepared from activated mixed lymphocyte cultures or with recombinant interleukin-1, a 10- to 15-fold increase in CAT activity was detected. Deletion analyses showed two regions of interest: a proximal region that enhanced CAT expression in a cell-specific manner and a distal region that conferred responsiveness to both conditioned media and recombinant interleukin-1. This distal responsive element had properties of an inducible transcriptional enhancer, and deletion of the proximal cell-specific region rendered the distal element responsive to stimulation by conditioned media in nonliver cells.